BepiColombo: A Platform for Improving Modeling of Electric Propulsion-Spacecraft Interactions - Filleul, Félicien; Sutherland, Orson; Cipriani, Fabrice; Charles, Christine (Frontiers in Space Technologies, 2021)
This paper provides the first results of a long term study aimed at improving the validity of numerical modeling techniques for Electric Propulsion induced Spacecraft Charging using the Spacecraft Plasma Interaction System software. The pre-flight numerical model of the European Space Agency's BepiColombo mission and its outputs are presented as a benchmark example of the present capabilities and limitations of the model. It is demonstrated that the code can obtain the spacecraft charging equilibrium by simulating the dynamic interactions between: the electric propulsion system, the thruster generated plasmas and spacecraft systems exposed to space. The importance of including a physical description of the electron cooling in the freely expanding thruster plasmas is shown by comparing simulations with different polytropic indexes. It particularly highlights the inadequacy of treating the entire plasma as isothermal. The reported variability of the simulation outputs with numerical and physical parameters opens up future improvements for pre-flight design modeling, as well as increased understanding of plasma thruster induced charging processes, through future comparison with available flight telemetries.